HERBAL DRUG-INDUCED ADVERSE DRUG REACTION: A CASE REPORT - Gari, Manju; Majhee, Lakhan; Kumari, Kavita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â The present study done to focus many adverse drug reactions unrecorded with either patients failing to present to health services due to herbal medicine or no pharmacovigilance analysis is being made. In this case, a 55-year-old female patient with 41 kg weight, she received herbal treatment for gastritis and menstrual disturbance since November 2015. After administration of drug, she suddenly developed 23 small vesicles over neck and upper chest. Few vesicles ruptured over 4â€“5 days and few gradually increased in size to form bulla. The use of herbal drug has increased tremendously across the world in recent times. Hence, it has become important for pharmacovigilance of herbal drugs and adverse effect issues for the consumers and health-care professionals as it is complex to analyze these products than the conventional pharmaceuticals. Safeâ€ and naturalâ€ cannot be used anonymously. Sufficient adverse drug monitoring of herbal drugs is as important as any other formularies.